Global Saturated Regulator with Variable Gains for Robot Manipulators - Brandon Sánchez-García; Fernando Reyes-Cortés; Basil Al-Hadithi; Olga Félix-Beltrán (Journal of Robotics and Control (JRC), 2021)
In this paper, we propose a set of saturated controllers with variable gains to solve the regulation problem for robot manipulators in joint space. These control schemes deliver torques inside the prescribed limits of servomotors. The gamma of variable gains is formed by continuous, smooth, and differentiable functions of the joint position error and velocity of the manipulator. A strict Lyapunov function is proposed to demonstrate globally asymptotic stability of the closed-loop equilibrium point. Finally, the functionality and performance of the proposal are illustrated via simulation results and comparative analysis against Proportional-Derivative (PD) control scheme on a two-degrees-freedom direct-drive robot manipulator.